Where did tropospheric ozone over southern Africa and the tropical Atlantic come from in October 1992? Insights from TOMS, GTE TRACE A, and SAFARI 1992 - Thompson, Anne M.; Pickering, K. E.; McNamara, D. P.; Schoeberl, M. R.; Hudson, R. D.; Kim, J. H.; Browell, E. V.; Kirchhoff, V. W. J. H.; Nganga, D. (AGU, 1996)
The seasonal tropospheric ozone maximum in the tropical South Atlantic, first recognized from satellite observations [Fishman et al., 1986, 1991], gave rise to the IGAC/STARE/SAFARI 1992/TRACE A campaigns (International Global Atmospheric Chemistry/South Tropical Atlantic Regional Experiment/Southern African Atmospheric Research Initiative/Transport and Atmospheric Chemistry Near the Equator-Atlantic) in September and October 1992. Along with a new TOMS-based method for deriving tropospheric column ozone, we used the TRACE A/SAFARI 1992 data set to put together a regional picture of the O₃ distribution during this period. Sondes and aircraft profiling showed a troposphere with layers of high O₃ (≥90 ppbv) all the way to the tropopause. These features extend in a band from 0° to 25°S, over the SE Indian Ocean, Africa, the Atlantic, and eastern South America. A combination of trajectory and photochemical modeling (the Goddard (GSFC) isentropic trajectory and tropospheric point model, respectively) shows a strong connection between regions of high ozone and concentrated biomass burning, the latter identified using satellite-derived fire counts [Justice et al., this issue]. Back trajectories from a high-O₃ tropical Atlantic region (column ozone at Ascension averaged 50 Dobson units (DU)) and forward trajectories from fire-rich and convectively active areas show that the Atlantic and southern Africa are supplied with O₃ and O₃-forming trace gases by midlevel easterlies and/or recirculating air from Africa, with lesser contributions from South American burning and urban pollution. Limited sampling in the mixed layer over Namibia shows possible biogenic sources of NO. High-level westerlies from Brazil (following deep convective transport of ozone precursors to the upper troposphere) dominate the upper tropospheric O₃ budget over Natal, Ascension, and Okaukuejo (Namibia), although most enhanced O₃ (75% or more) equatorward of 10°S was from Africa. Deep convection may be responsible for the timing of the seasonal tropospheric O₃ maximum: Natal and Ascension show a 1- to 2-month lag relative to the period of maximum burning [cf. Baldy et al., this issue; Olson et al., this issue]. Photochemical model calculations constrained with TRACE A and SAFARI airborne observations of O₃ and O₃ precursors (NOx, CO, hydrocarbons) show robust ozone formation (up to 15 ppbv O₃/d or several DU/d) in a widespread, persistent, and well-mixed layer to 4 km. Slower but still positive net O₃ formation took place throughout the tropical upper troposphere [cf. Pickering et al., this issue (a); Jacob et al., this issue]. Thus whether it is faster rates of O₃ formation in source regions with higher turnover rates or slower O₃ production in long-lived stable layers ubiquitous in the TRACE A region, 10–30 DU tropospheric O₃ above a ∼25-DU background can be accounted for. In summary, the O₃ maximum studied in October 1992 was caused by a coincidence of abundant O₃ precursors from biomass fires, a long residence time of stable air parcels over the eastern Atlantic and southern Africa, and deep convective transport of biomass burning products, with additional NO from lightning and occasionally biogenic sources.